Hereditary and environmental determination of morphological characteristics of newborns - Młodziejowska, Romana (Anthropological Review, 1980)
The material for this study consists of 531 newborns (296 male and 235 female) born in 1978 in Warsaw. Body weight, length, head and chest circumferences were measured in newborns as well as in their mothers. Furthermore blood groups (ABO and Rh) were determined. Variability of the above traits was studied with respect to its relation to selected endo- and exogenous factors: mother’s age, father’s age, education of parents, marital distance, duration of marriage, duration of pregnancy, mode of delivery, parity (taking into account both pregnancies and live births). Each of these factors was categorized, everages of metrical characteristics of newborns by factor categories are presented in tables 1 and 2.A complex evaluation of a share of separate factors in formation of metric characteristics of newborns by means of one way analysis of variance has shown (table 3) that, besides sex of a newborn, the most clear influences are from parents’ education, parity, marital distance, mother's blood group. Mother's age operates in a slightly weaker way and the weakest is influence from mode of delivery.